The Outcome of Non-cardiac Surgery among Children with Congenital Heart Disease: A Single Institution-based Review of Cases in the Low-Resource Setting - Zemenu Temesgen; Tamirat Moges (The Annals of African Surgery)
Background: Over half of infants with congenital heart disease (CHD) need surgery for non-cardiac abnormalities during the first year of life. Objective: This study looked at the variables and surgical outcomes related to non-cardiac surgery in this specific patient population. Materials and methods: We looked at and analyzed 152 case records using SPSS software version 27 (SPSS Inc., Chicago, IL, USA) in order to identify factors associated with post-operative mortality on the 7th and 30th days using a binary and multivariable logistic regression model. Results: Infants with CHD who had non-cardiac surgery for non-heart-related abnormalities had mortality rates of 28.9% on the 7th, and 45.4% on the 30th post-operative day. Preterm neonates had a 2.16-fold higher mortality rate than mature neonates. The death rate was 1.2 times higher in patients who underwent surgery after 24 hours of diagnosis than those who had before 24 hours. Death is also associated with severe CHDs, comorbidities, genetic diseases, operating room mishaps, and age <1 year. Conclusion: The study found that among CHD cases undergoing non-cardiac surgery, the mortality rate was quite high on the 7th and 30th post-operative days.